Strategi Pemasaran Pada Produk Pembiayaan Kesejahteraan Pegawai (PKP) Di Bank Jawa Barat Dan Banten Syariah - Anggraini, Rini; Putra, Purnama (LPPM Universitas Islam 45, 2025)
Companies and banks are required to be able to make marketing strategies in providing or improving services to customers so that the company's goals can be achieved. The applied marketing strategy must be reviewed and developed in accordance with market developments and the market environment. The purpose of this study is to determine the Marketing Strategy Analysis of Employee Welfare Financing Products (PKP) at Bank Jawa Barat and Banten Syariah Sub-Branch Office Cikarang. This study uses a combination method (Mix Methods). Data is analyzed through SWOT analysis. From the research results show that there are internal factors and external factors of Bank BJB Syariah KCP Cikarang in marketing the product of Employee Welfare Financing (PKP). Bank BJB Syariah KCP Cikarang in marketing Employee Welfare Financing (PKP) products applies a 4P Marketing mix, namely Product, Price, Place and Promotion. Based on the results of the scoring weighting that has been done through the IFE matrix and the EFE matrix, it is known that the identified internal factors and external factors are 1.02 and -0.08, so the results are that Bank BJB Syariah KCP Cikarang is in quadrant 2 position where Bank BJB Sharia KCP Cikarang in marketing PKP products is in a strong position but still has to face challenges or threats. Marketing strategy analysis resulting from the SWOT analysis method with the SWOT matrix conducted by Bank BJB Syariah KCP Cikarang in the face of competition with other banks that have similar financing products, namely by creating a strong Brand Image, increasing PKP product promotions both through publications and socialization.